Examination of the American grapevine leafhopper (Scaphoideus titanus Ball) in Debrecen and Micske (Misca, West Romania) - Szalárdi, Tímea; Nagy, Antal; Tarcali, Gábor (Acta Agraria Debreceniensis, 2014)
Grapevine flavescence dorée (FD) was detected first in Hungary in 2013 in Zala County (South-West-Hungary). The disease is a serious danger for grapevine growing and grapevine propagating production. In 2014, the pathogen has been found in several new places in Hungary, viz. in Vas and Fejér Counties, and it was also detected in the former location in Zala County. The american grapevine leafhopper (Scaphoideus titanus) is the main vector of the disease. This pest was detected first in Hungary in 2006 and then it has spread all over the country. Since we have not detailed distribution data of this pest in surroundings of Debrecen, therefore we made observations in this region in 2014. The presence of the pest was confirmed by yellow sticky cards in two locations in Debrecen and another site in West Romania near to Hungarian border. We found that S. titanus is present in each sampled sites that cause serious potential danger for the appearance and spread of Grapevine flavescence dorée (FD) in this region.